La educación inicial y su importancia en el cuidado del medio ambiente con los niños/as de inicial 2 paralelo “b” de la Unidad Educativa Federico González Suárez de la parroquia San Miguel, cantón Salcedo provincia de Cotopaxi en el año lectivo 2014-2015 - Flores Toapanta, María Amparo (2015)
The importance of environmental care is a debate that tries to eliminate environmental pollution, conservation of nature is an active part of the early experiences of infants, the environment is the place of habitat and development comprehensive, through the workshops helped decrease a percentage of organic and inorganic waste generated with no control, it should be noted that educational establishments will promote themes that benefit children early education for participatory in society, to live in harmony and peace with the environment. With Infant workshops they achieved the key objective is to protect and care for the environment around them and got the child to enjoy a healthy and sustainable environment, through education reaches promote environmental relevance, furthermore Children are responsible citizens, participating in the care of the natural environment, which are surrounded in their daily lives.